The dark side of liquidity: shedding light on dark pools' marketing and market-making. Issue 4 (3rd July 2020) - Lagna, Andrea; Lenglet, Marc
ABSTRACT: In this article, we explore the case of dark pools of liquidity, which are trading venues that do not display order books and other trading-related data. We argue that, in a context where liquidity remains essentially invisible, dark-pool providers use visual advertisements that iconically represent liquid markets. In so doing, they defuse the idea that dark liquidity is harmful to market efficiency and fair pricing. We use Barthesian and Greimasian semiotics to study how a major bank advertised its dark-liquidity services through iconic visual signs. We contribute to economic sociology and social studies of finance by foregrounding the role of visual advertising in the construction of liquid markets. To do so, we draw on insights from market studies and visual culture.